MANAJEMEN SYARIAH DALAM PRAKTEK PENGUPAHAN KARYAWAN PERUSAHAAN SYARIAH - Arijulmanan (JURNAL ALAMIAH, 2020)
Sharia Management in the Practice of Paying Employees of Sharia Companies (Case Study of PT. Asuransi Takaful Umum). Shari'ah management is a management based on the provisions of Allah Ta'ala. The focus of the problem in this research is how to form employee wages with sharia management that is able to support the strategy of PT. General Takaful Insurance in achieving the stated targets. The approach used in this research is descriptive analytical method, through library research and observation.The results of observations about the wages of employees at PT Asuransi Takaful General indicate that the wage program run by the company is a wage program that is determined based on a mutual agreement between the company and employees with reference to the verses of the Qur'an and the Hadith of the Prophet. Shari'ah management has been applied in the practice of wages at PT ATU. This is proven by the implementation of the Collective Labor Agreement (PKB) which is an agreement between the company management and employees based on the Qur'an and Al-Hadith.The wage law for employees in the Islamic view is to save the interests of both parties between the company and the employee, between the employer and the worker. Wages are determined by not oppressing each other, but by being honest and fair with each other between the company and employees. Each employee will be rewarded according to what he does in the production process. Likewise with Takaful employees, if they are productive, they will get wages as compensation according to their productivity. The suitability of sharia management in providing wages to PT ATU employees can be seen clearly from the types of wages provided such as overtime pay when working hours, health benefits, transportation allowances, meal allowances, etc. All types of wages are in accordance with Islamic teachings in their determination. In practice at PT ATU in the wage component there is still no education allowance, housing allowance and expertise allowance.